2017
DOI: 10.1016/j.jphs.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clozapine on adipokine secretions/productions and lipid droplets in 3T3-L1 adipocytes

Abstract: Clozapine, a second-generation antipsychotic (SGA), is a cause of side effects related to metabolic syndrome. The participation of serotonin 5-HT and histamine H receptors in the central nervous system has been reported as a mechanism of the weight gain caused by clozapine. In the present study, we investigated the direct pharmacological action of clozapine on the 3T3-L1 adipocytes and compared it to that of blonanserin, an SGA with low affinity for both receptors. Short-term exposure to clozapine decreased se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Indeed, in their study, short and long-term exposure to clozapine significantly decreased secretion of leptin and its mRNA expression [91]. More specifically, while investigating the mechanisms of this decreased metabolism of leptin pertaining to clozapine, the authors found that a selective serotonin 5-HT2c antagonism significantly enhances the lowered secretion of leptin triggered by clozapine when compared to controls [91]. According to their findings, this was not the case for histamine H1 antagonism [91].…”
Section: Leptin and Antipsychotics-induced Weight Gainmentioning
confidence: 93%
See 4 more Smart Citations
“…Indeed, in their study, short and long-term exposure to clozapine significantly decreased secretion of leptin and its mRNA expression [91]. More specifically, while investigating the mechanisms of this decreased metabolism of leptin pertaining to clozapine, the authors found that a selective serotonin 5-HT2c antagonism significantly enhances the lowered secretion of leptin triggered by clozapine when compared to controls [91]. According to their findings, this was not the case for histamine H1 antagonism [91].…”
Section: Leptin and Antipsychotics-induced Weight Gainmentioning
confidence: 93%
“…They concluded that clozapine, but not blonanserin, strongly and directly interacts with leptin secretion (as well as other adipokines' secretion) and adipocytes enlargement. Thus, this drug's effect on metabolic disturbances is also linked to a direct action on adipocytes mechanism of the regulation of food intake [91]. Indeed, in their study, short and long-term exposure to clozapine significantly decreased secretion of leptin and its mRNA expression [91].…”
Section: Leptin and Antipsychotics-induced Weight Gainmentioning
confidence: 99%
See 3 more Smart Citations